"Wild" Tariff Schemes: Evidence from the Republic of Georgia - Anna Alberini; Levan Bezhanishvili; Milan Scasny (Charles University in Prague, Institute of Economic Studies (IES), 2021)
Consumers often struggle to grasp complicated pricing plans, including increasing block rate (IBR) schemes, which have been used for decades by utilities in many parts of the world. The assumption that they encourage conservation has, however, recently been challenged (Ito, 2014). We take advantage of the unique IBR tariffs for electricity in the Republic of Georgia-where "overage" is penalized more heavily than in conventional IBRs-to ask whether consumers respond to price, and to which price specifically. Based on the data from several waves of the Georgia Household Budget Survey, we find evidence of "notches," namely missing probability mass on the right of the lowest block cutoff and a spike in the frequency of monthly consumption to the left of it. This is in contrast with the "bunching" pattern predicted by Borenstein (2009) when demand is not completely inelastic, and with the empirical evidence in Borenstein (2009) and Ito (2014). During our study period (2012-2019), the tariffs were revised-both downwards and upwards-to a different extent in different blocks and at different times across the regions of the country. We devise difference-in-difference study designs that exploit such natural experiments, finding that consumption did increase when the tariffs were reduced and fell when they were raised. Ours is one of the few studies that exploits quasi experimental conditions to examine whether the response to price changes is symmetric. We find that it is, in that the implied price elasticity of electricity demand is in both cases -0.3. Finally, we fit an electricity demand function, which results in an even stronger price elasticity (-0.5). Households seem to respond to the actual, average price (here equal to the marginal price) rather than to expected price. Our estimates of the price elasticity bode well for a carbon tax, an energy tax, or simple tariff increases to help curb imports of gas-fired electricity from neighboring countries.
Keywords: D12; Q41; Q48; 330; residential electricity demand; price elasticity; increasing block rates; tariff schemes; asymmetric response to price changes